PENGARUH PENGGUNAAN MEDIA MOBILE LEARNING PADA MATERI USAHA DAN ENERGI TERHADAP HASIL BELAJAR SISWA KELAS X DALAM PEMBELAJARAN FLIPPED CLASSROOM - Angraini, Reka; Riswanto, Riswanto; Salim, M Barkah (Universitas Muhammadiyah Metro, 2023)
Abstract: Students' difficulties in understanding physics subjects, especially material that often occurs in everyday life, namely work and energy, as well as limited face-to-face learning time in class (3 x 25 minutes) require students to study more independently at home or learn using the flipped classroom model. This study aims to determine the effect of the use of mobile learning media on work and energy materials on the learning outcomes of class X students in flipped classroom learning. The method used is experimental, with nonequivalent control gorub design and sampling with simple random sampling technique. The subjects of this study were class X Mia 2 as an experimental class with a total of 36 students and X Mia 4 as a control class with a total of 36 students. The test instrument used is an essay question with 10 questions. The research data were obtained from the difference in the pretest-posttest learning outcomes of the two classes. The results of the study: Testing the hypothesis using the independent sample t-test shows a value of Sig.0.001 > 0.05 and t_count (3.606) > t_table (1.994) so that it can be concluded that there is a difference in the average student learning outcomes of the experimental class and the control class. The N-gain score test shows that the use of mobile learning media in the experimental class is quite effective (58%) and the use of power point media in the control class is less effective (49%). So it can be concluded that there is an effect of the use of mobile learning media on work and energy material on the learning outcomes of class X students in flipped classroom learning. Based on the results of this study, teachers are expected to be able to choose learning media that are appropriate to the circumstances of the school environment, and students are expected to be more active and enthusiastic in learning and to be able to utilize the learning media that have been provided by the teacher so that they are able to develop their potential to achieve optimal learning outcomes.